(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Stock markets in India serves the companies by giving them the much-required funds for their long-term needs and at the same time providing the investors an opportunity to park their excess money in this market and experiencing the maximization of wealth which in turn gives them a chance to be the part of nation’s development hence any stock market plays a vital role in economic development. In the recent past, Indian stock market has observed slight slowdown and is being affected due to economic upheavals occurring worldwide. The present study focuses on the trends of Indian security market based on the total number of listed companies, number of sub brokers, shares traded, capital raised in specific industries, average shares price annually etc. during the study period from 2013-2018-19. Also, by examining the investors grievances addressed and investigations carried out by the market regulators i.e., SEBI, the study concludes, although number of companies listed have increased considerably on BSE and reasonable amount of sub-brokers have also registered on security market still there is a declining trend observed in the quantity of total shares traded in cash segment in all during the study period. The present study recommends that brokers, sub-brokers and even the educational institutes may conduct investment awareness programs for more integrated approach and to attract more of the investors towards security market.